Smokeless tobacco (snus) is associated with an increased risk of type 2 diabetes: results from five pooled cohorts. (6th February 2017) - Carlsson, S.; Andersson, T.; Araghi, M.; Galanti, R.; Lager, A.; Lundberg, M.; Nilsson, P.; Norberg, M.; Pedersen, N. L.; Trolle‐Lagerros, Y.; Magnusson, C.
Abstract: Background: Smoking and nicotine exposure increase insulin resistance and the risk of type 2 diabetes. Swedish smokeless tobacco (snus) is high in nicotine, and its use is prevalent in Scandinavian countries, but few studies have investigated snus use in relation to diabetes risk. Objective: To explore the association between snus use and risk of type 2 diabetes using pooled data from five cohorts. Methods: Analyses were based on prospective studies conducted between 1990 and 2013 including 54 531 never‐smoking men and 2441 incident cases of type 2 diabetes identified through screening, self‐reporting and hospital and prescription registries. Hazard ratios (HRs) and 95% confidence intervals (CIs) were assessed and adjusted for age, body mass index, educational level, alcohol consumption and physical activity. Results: Compared to never users, the HR of type 2 diabetes was 1.15 (95% CI: 1.00–1.32) in current users of snus. In individuals consuming 5–6 boxes per week, the HR was 1.42 (95% CI: 1.07–1.87); in those consuming ≥7 boxes per week, the HR was 1.68 (95% CI: 1.17–2.41). Each additional box of snus consumed per week yielded an HR of 1.08 (95% CI: 1.01–1.16). Conclusion: Our findings indicate that high consumption of snus is a risk factor for type 2 diabetes. The risk was similar to that in smokers, implying that smokers will not reduce their risk of type 2 diabetes by changing to snus use. The results also support the notion that nicotine increases the risk of type 2 diabetes.